ZAGRANICZNE STUDIA I STYPENDIA NAUKOWE ROMANISTÓW UNIWERSYTETU JANA KAZIMIERZA WE LWOWIE - Wiaderna-Kuśnierz, Renata (Zeszyty Prawnicze, 2016)
In this article I present the Roman Law scholars of the Jan Kazimierz University of Lwów and their travel abroad for the purposes of scholarship. Lwów’s scholars developed their knowledge and skills by working with prominent German, Austrian, French and Italian personalities in legal studies. The scholarships awarded by the Emperor Franz Joseph I Foundation (Fundacja im. Cesarza Franciszka Józefa I), the National Culture Fund (Fundusz Kultury Narodowej), and the Emil Parnas Foundation (Fundacja im. Emila Parnasa) helped them to further their education abroad. Leon Piniński and Marceli Chlamtacz, professors of the Jan Kazimierz University, studied abroad in the late 19th century. Leon Piniński went to universities in Leipzig, Berlin and Vienna, where he worked with Heinrich Dernburg and Bernhard Windscheid. Marceli Chlamtacz travelled to Vienna and Berlin, where he collaborated with Professors Franz Hofmann, Adolf Exler, and Alfred Pernice. Professor Wacław Osuchowski studied abroad in the early 1930s, first in Rome, and subsequently in Munich and Paris. The fourth of the scholars presented in the article, Dr. Edward Gintowt-Dziewałtowski, a research assistant in the Chair of Roman Law, spent four years in Vienna, Innsbruck, Rome, and Palermo in the 1930s.